Workshop Pelatihan Penulisan Berita untuk Majalah Dinding untuk Siswa SMA Fides Kefamenanu - Mikhael Misa; Anselmus Sahan; Eugelin Sulaiman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this study is to explore the benefits of extracurricular journalism activities on students' academic ability, especially in the aspect of language. A community service activity was carried out to provide news and opinion training for wall magazines to students of class XI at Fides Quaerens Intellectum (FQI) Kefamenanu Catholic Private High School. A total of 25 students of SMAK FQI participated in filling out a questionnaire covering eight main aspects, related to 1) reasons for choosing wall magazine training (mading), 2) understanding of mading, 3) implementation of a wall magazine, 4) benefits of additionalcurricular journalism on academic aspects (language), 5) benefits of Extracurricular Journalism on creative, innovative, and productive aspects, and 6) benefits of Additionalcurricular Journalism On Psychomotor Aspects. The results of the above analysis show that journalism training has a positive impact on students. Therefore, this can be the basis for further development and improvement in the organization of extradisciplinary journalism activities in schools to provide more beneficial experiences for students.